2017
DOI: 10.1002/cam4.1176
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P62 in hepatocellular carcinoma involving hepatitis B virus infection and aflatoxin B1 exposure

Abstract: This study aims to clarify the relationship and mechanism between expression of autophagy‐related protein P62 and prognosis of patients with hepatocellular carcinoma (HCC) involving chronic hepatitis B virus (HBV) infection and aflatoxin B1 (AFB1) exposure. HCC patients who underwent resection were divided into three groups: HBV(+)/AFB1(+) (n = 26), HBV(+)/AFB1(−) (n = 68), and HBV(−)/AFB1(−) (n = 14). The groups were compared in terms of mRNA and protein levels of P62, disease‐free survival (DFS), and overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…Numerous studies report different p62 expression patterns in different types of human cancers of different origins: the protein is overexpressed in prostate, digestive system, liver and lung carcinoma or down‐regulated in oesophageal adenocarcinomas and colorectal cancers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies report different p62 expression patterns in different types of human cancers of different origins: the protein is overexpressed in prostate, digestive system, liver and lung carcinoma or down‐regulated in oesophageal adenocarcinomas and colorectal cancers …”
Section: Discussionmentioning
confidence: 99%
“…To add a further layer of complexity studies mainly focused on human in pancreatic ductal carcinoma suggest that both p62 overexpression in cancer cells and its down regulation in tumour microenvironment promote tumour . In contrast, elevated p62 levels in the stroma seem to induce tumour suppression by intertwined anti‐inflammatory/metabolic responses . Thus, homeostatic maintenance of p62 in both cancer and stroma seems to dictate the final outcome of the tumorigenic process .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, deletion of p62 or NRF2 in mice with liver-specific ATG7 or ATG5 deficiency decreased liver tumor development, implying that the p62-KEAP1-NRF2 axis contributes to tumorigenesis [26,30]. Moreover, p62 accumulation and NRF2 activation were found in HCC patients and were correlated with a poor overall survival rate in HCC caused by HBV and aflatoxin B1 [31,32]. Thus, the p62-KEAP1-NRF2 axis could serve as the key driver of human HCC.…”
Section: Role Of Autophagy In Hccmentioning
confidence: 99%
“…the most important cause for this high AIR and ADR [1]. AFB1 is a known I-type chemical carcinogen produced by Aspergillus parasiticus and Aspergillus flavus, and has been proved to involve in the carcinogenesis and progression of HCC [4][5][6][7][8][9][10]. This carcinogenicity of AFB1 mainly results from its metabolic product binding to DNA and inducing DNA damage.…”
Section: Cancer Prognosismentioning
confidence: 99%
“…These products of AFB1, especially AFBEX, are characterized by high reaction, genic toxicity, and carcinogenicity [3]. Evidence from molecular epidemiology and animal models has shown that AFB1 is an important carcinogen inducing hepatocellular carcinoma (HCC) [4][5][6][7][8][9][10]. Mechanically, the carcinogenesis of AFB1-related HCC mainly involves in the formation of DNA damage (including AFB1-DNA adducts, DNA single-strand breaks, DNA double-strands breaks, and gene mutations), the inactivation of such tumor suppressor gene as TP53, and the activation of cancer genes such as Ras [3,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%